Final answer:
The exact value of sin(11pi/12)cos(pi/6)-cos(11pi/12)sin(pi/6) is 1/2 - 1/2√(2 + √3).
Step-by-step explanation:
To find the exact value of sin(11π/12)cos(π/6)-cos(11π/12)sin(π/6), we can use the trigonometric identity sin(A-B) = sinAcosB - cosAsinB. This will allow us to simplify the expression.
Let's substitute the values for A = 11π/12 and B = π/6:
- Sin(11π/12 - π/6) = sin(5π/12) = ½√(2 - √3)
- Cos(11π/12 - π/6) = cos(5π/12) = ½√(2 + √3)
Now we can substitute these values into the expression:
Sin(11π/12)cos(π/6) - cos(11π/12)sin(π/6) = ½√(2 - √3) * ½ - ½√(2 + √3) * ½
Simplifying further, we get: ½ - ½√(2 + √3)